The initiation of translation in E. coli: apparent base pairing between the 16srRNA and downstream sequences of the mRNA. - Sprengart, M L (1990)
Bacteriophage T7's gene 0.3, coding for an antirestriction protein, possesses one of the strongest translation initiation regions (TIR) in E. coli. It was isolated on DNA fragments of differing length and cloned upstream of the mouse dihydrofolate reductase gene in an expression vector to control the translation of this gene's sequence. The TIR's efficiency was highly dependent on nucleotides +15 to +26 downstream of the gene's AUG. This sequence is complementary to nucleotides 1471-1482 of the 16srRNA. Similar sequences complementary to this rRNA region are present in other efficient TIRs of the E. coli genome and those of its bacteriophages. There seems to be a correlation between this sequence homology and the efficiency of the initiation signals. We propose that this region specifies a stimulatory interaction between the mRNA and 16srRNA besides the Shine-Dalgarno interaction during the translation initiation step.